Retrieval of tropospheric column-averaged CH4 mole fraction by solar absorption FTIR-spectrometry using N2O as a proxy - Z. Wang; N. M. Deutscher; T. Warneke; J. Notholt; B. Dils; D. W. T. Griffith; M. Schmidt; M. Ramonet; C. Gerbig (Atmospheric Measurement Techniques, 2014)
Tropospheric column-averaged CH4 mole fractions were derived from ground-based column absorption measurements. The method uses stratospheric N2O columns to correct for the stratospheric contribution to the CH4 total column. The method was applied to four Total Carbon Column Observing Network (TCCON) sites covering locations from the Northern Arctic to the tropics. It performs well for all sites. The derived tropospheric CH4 concentrations were compared with profiles measured by aircraft at three sites. The results indicate an inter-site consistency within 6 ppb (~0.3%). With aircraft profiles up to 3 km, the seasonal behavior of the derived tropospheric CH4 concentration was also checked, revealing a difference of around 20 ppb. The mean relative uncertainty of the four sites, as estimated from the daily standard deviations, is 0.23%.